Community and social support networks as a resource for health care and health maintenance - Pérez Becerra, Francy Nelly; Aarón Movilla, Elkin Enrique (Subcomité editorial y de evaluación de obras de la Facultad de Ciencias de la Salud Editora Revista Dra. Bibiana Matilde Bernal Gómez, 2020)
The Community networks , as an open system of dynamic exchange among the members of a social group (family, neighborhood, association or institution), make it possible to enhance resources for the care and maintenance of a individual's health but those ones can also become in a source of discomfort, stress and illness. Objective: To understand the dynamic of community networks and social support as a resource for the care and maintenance of health (promotion, education and prevention) in some families of the “Los Patriotas” neighborhood in the Tunja city. Methodology: Qualitative research / intervention, based on the participant observation and the reports of 110 research records of 15 UPTC Family Medicine Resident Physicians in their community practice in the Los Patriotas neighborhood in the Tunja city. For this category of analysis, the following items were assumed: The Community and social support networks as family, friends, neighbors, peer groups, social organizations and institutions ( health service, police and educational institutions ... ) Conclusion: The Community and social support groups are relevant due to the support that they provide to society, for the contributions and strong connections for the common interest, such as improving the quality of life and the health of people and communities; This is what prioritizes the importance of community projects in spaces of collective construction and strengthening of any social group.